(untitled) (Bulletin KNOB, 2010)
In the first half of the 19th century no theoretical education for architects existed in the Netherlands, but since 1817 there was a Royal Academy of Fine Arts in Amsterdam where, among other subjects, architecture was taught. In 1837 the academy held a special competition for a city theatre, which was won by the Amsterdam carpenter’s son Robertus van Zoelen (1812-1869). On the basis of a prescribed programme the competitors had to make a sketch first, and subsequently they were given one month’s time to design more accurate construction drawings. In this article earlier and later competitions are dealt with, the architectonic design and the layout of these theatres, which could accommodate approximately 1500 visitors. Van Zoelen’s creation was uncommonly monumental for Dutch standards and was hardly comparable to the wooden theatre of city architect Jacob Eduard de Witte situated on Leidseplein in Amsterdam at that time. The author discusses other theatres in the Netherlands and Europe. Since around 1750 good acoustics and visibility for all the visitors were aimed at, the form of the stage in connection with this, as well as the external recognizability of the theatre by means of an entrance under a column portico. There were advanced designs in several European cities and Van Zoelen had heard of them, but no more than that. It is likely that he never crossed the national borders and derived his knowledge from books and colleagues, such as the managing director of the Amsterdam academy Martinus Gerardus Tétar van Elven. Just as at the French academy of architecture, which served as an example for the Dutch academy in many respects, the competitions were highly academic and theoretical in character.